Sidenafil protocols for the treatment of ICC: A literature review (International Seven Journal of Health Research, 2023)
A literature search was conducted on the effects of sidenafil and the protocols used in heart failure. The phosphodiesterase-5 inhibitor stands out as a new drug in the cardiologic therapeutic arsenal, since the action of inhibiting the various types of phosphodiesterase causes an increase in cAMP and cGMP in white tissues.DOI:https://doi.org/10.56238/isevjhv2n2-014